Optimizing antimicrobial routes: risk factor analysis for intravenous therapy in children with preseptal orbital cellulitis - Roberto Privato; Emanuela Inserra; Francesco Pezzoli; Alessia Nucci; Stefano Masi; Elena Chiappini; Giuseppe Indolfi; Sandra Trapani; Luisa Galli; Elisabetta Venturini (Italian Journal of Pediatrics)
Abstract Background The optimal route of antimicrobial administration for preseptal orbital cellulitis (OC) in children remains uncertain. While mild cases may be managed with oral therapy, distinguishing between mild and severe presentations is challenging. The recently proposed ASSET score offers a tool for assessing the severity of skin and soft tissue infections, but prospective validation in large cohorts of preseptal OC is lacking. As a result, most patients with periorbital infections are admitted for intravenous (IV) antibiotics. This study aims to identify clinical and laboratory features predictive of severe preseptal OC requiring IV treatment. Methods A retrospective study was conducted at Meyer Children’s Hospital IRCCS, Florence, reviewing outpatient records for OC cases from January 2017 to June 2024. Data on age, sex, clinical presentation, blood tests, and management were collected. Results Previously initiated oral therapy was associated with the need for IV therapy (p < 0.001), as well as the presence of fever (p < 0.001), and severe eyelid swelling (p < 0.001). The median ASSET score was higher in patients with preseptal OC requiring IV therapy (p < 0.001). Differences in laboratory findings were noted between children with preseptal OC managed with and without IV antibiotics. Conclusions Previous trials of oral antibiotics, systemic features, and severe swelling influence clinicians’ decisions to initiate IV antibiotics in preseptal OC. If validated for preseptal OC, the application of the ASSET score could significantly reduce the number of children treated with IV antibiotics. Ancillary blood tests may be useful for detecting preseptal OC requiring IV treatment.